Rancang Bangun Alat Ukur Berat Badan Dan Tinggi Badan Berbasis Arduino (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2021)
This research aims to develop an Arduino-based weight and height measurement tool, then test an Arduino-based weight and height measurement tool with conventional measuring devices, and create a database on an Arduino-based weight and height measurement tool. This research was carried out in the L1 Building, Faculty of Engineering, Jakarta State University, an electronics engineering laboratory, and at the researcher's house (due to the COVID-19 pandemic). When the research was conducted in December 2019 - July 2020. Researchers used references to body mass index from the Ministry of Health in 2014, then used loadcell sensors as input for weight, ultrasonic sensors as input for height, and Arduino mega 2560 as a microcontroller. For the output, the researchers used an LCD touchscreen that displays information visually and speakers that provided information on body weight, height, and body mass index status audio. To send data resulting from information, researchers used esp8266-01 as a communication tool with a microcontroller to be sent to a database on a laptop or PC that has been installed Xampp with the help of a smartphone connection as a hotspot. The results of this study indicate that the Arduino-based Weight and Height Measuring Instrument results can measure weight from a minimum of 18 kg to a maximum of 74 kg and measure height from a minimum of 115 cm to a maximum of 176 cm that has been compared with the GEA reference brand measuring instrument with error for weight of 0.86% and height of 0.75%.